PERAN KEMENTERIAN DALAM NEGERI DALAM PENGEMBANGAN EKOWISATA DI INDONESIA - Resti Meilani; E.K.S Harini Muntasib (Department of Forest Resources Conservation and Ecotourism - IPB University, 2013)
Ecotourism was seen as a green alternative of activity in tourism industry with widely open opportunity, which assumed to be able to increase the state and local government revenue, provide job opportunity, and give considerable multiplier effect. The complexity of ecotourism phenomenon as a system required that each stakeholder involved in ecotourism having a shared goal and synergy. Ecotourism development should be supported by each stakeholder, by performing effectively within their role and function. The research was aimed at identifying the role and function of The Indonesian Ministry of Home Affairs (MHA) in ecotourism development in Indonesia. Qualitative research approach was employed in the research. Data was collected through interview with key informant at the MHA. Result showed that the MHA had played its role in Indonesian ecotourism development by issuing a regulation which provides a framework for local government to develop their potential in to ecotourism supply, and conducting measures needed to assist local government in the implementation of the regulation. Keywords: ecotourism, development, indonesia, ministry of home affairs, role